Phenotypic variability within the desminopathies: A case series of three patients - Yeow, Dennis; Katz, Matthew; Henderson, Robert; Prasad, Sandhir; Denman, Russell; Blum, Stefan; Davis, Mark; Robertson, Thomas; McCombe, Pamela (Frontiers in Neurology, 2023)
The DES gene encodes desmin, a key intermediate filament of skeletal, cardiac and smooth muscle. Pathogenic DES variants produce a range of skeletal and cardiac muscle disorders collectively known as the desminopathies. We report three desminopathy cases which highlight the phenotypic heterogeneity of this disorder and discuss various factors that may contribute to the clinical differences seen between patients with different desmin variants and also between family members with the same variant.